2021
DOI: 10.3390/nano11051270
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic ZnO Nanoparticles Synthesized Using a Novel Plant Extract: Application to Enhance Physiological and Biochemical Traits in Maize

Abstract: The need to increase crop productivity and resistance directs interest in nanotechnology. Indeed, biogenic metal oxide nanoparticles can promote beneficial effects in plants, while their synthesis avoids the environmental impacts of conventional synthetic procedures. In this context, this research aimed to synthesize biogenic zinc oxide nanoparticles (ZnO-NPs) using, for the first time, an extract of a wild and spontaneous aquatic species, Lemna minor (duckweed). The effectiveness of this biogenic synthesis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 66 publications
2
53
0
Order By: Relevance
“…Finally, Zn was slightly increased by the highest dosage, BIO 1. Increases in the content of this element could be of relevance as Zn is involved in chlorophyll biosynthesis and chloroplast development [30,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Zn was slightly increased by the highest dosage, BIO 1. Increases in the content of this element could be of relevance as Zn is involved in chlorophyll biosynthesis and chloroplast development [30,70].…”
Section: Discussionmentioning
confidence: 99%
“…Lemnaceae are plants rich in metabolites that exhibit antioxidant and antibacterial properties [29]. In addition, duckweed has been recently demonstrated to possess a high content of phenolic acids, phenols and flavonoids [26,30]. It is well known that certain compounds could benefit plants when exogenously applied [31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zn can induce the production of secondary metabolites, which can positively affect the first stage of seeds’ development [ 44 , 45 ]. In particular, seed attributes can be improved by ZnO-NP for its electronic characteristics, which can give rise to the photosensitization and photogeneration of ROS [ 46 ]. Consequently, this improves oxygen imbibition and water absorption by seeds, thus allowing faster and ameliorated seed germination [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for root fresh weight, all the treatments stimulated this trait on treated plants, with T4 showing a remarkable effect. Priming with nanomaterials may also benefit seedlings by stimulating plant growth and defensive mechanisms, which were mainly related to increased antioxidant properties [ 46 ]. The mechanism by which ZnO-NP activates these processes is still largely unknown and under debate; however, several studies have shown that this material can improve the performance of the treated species at low dosages, increasing root and shoot biomass [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nanotechnology is an important rising field, owing to several important functions in copious research areas [1]. Nanoparticles (NPs) have special characteristics due to their small size (less than 100 nm) which results in lofty surface areas and charges; therefore, NPs are highly reactive over their bulk scale counterparts [2][3][4].…”
Section: Introductionmentioning
confidence: 99%